Status Quo and Prospect of Multi-source Heterogeneous Data Fusion Technology for New Power System - Zhen WANG; Dong LIU; Chongyou XU; Jiaming WENG; Fei CHEN (Zhongguo dianli)
In the context of energy transition, the new power system is being built continuously with the goal of being clean and low-carbon, open and interactive. With the fast development of monitoring technology and communication technology, the data sources of power system have become more diverse and the structures of the data have become more complex, which provides a data basis for and at same time brings new challenges to the new power system data fusion. Firstly, the data characteristics of the new power system are analyzed and the data fusion requirements of the new power system are proposed. Then the data model of the new power system and the hierarchical division of multi-source heterogeneous data fusion technologies are introduced, and the advantages and limitations of the key fusion technologies and their applicable scenarios are analyzed. The data requirements, data sources, fusion objectives, common methods and research difficulties of multi-source heterogeneous data fusion technologies are summarized under five typical scenarios, including transmission and distribution collaboration, source-grid-load-storage collaboration, virtual power plants, multi-type loads, and electricity-carbon trading. Finally, the future prospects of the new power system data fusion technology are explored.